Anammox reactor exposure to thiocyanate: Long-term performance and microbial community dynamics. (December 2020) - Yu, Xiaolong; Nishimura, Fumitake; Hidaka, Taira
Graphical abstract: Highlights: Effects of thiocyanate (SCN − ) on anammox reactors were assessed. SCN − ≥ 100 mg L −1 exposure led to failure of denitrification by anammox processes. The SCN − -degrading bacteria competed with the anammox species for NO2 – . SCN − exposure changed the microbial community in the anammox reactors. Thiobacillus was the dominant genus in the reactor with SCN − addition. Abstract: Anaerobic ammonium oxidation (anammox) is an autotrophic denitrification process that has broad application potential for treating coking wastewaters. The present study estimated the effects of thiocyanate (SCN − ), a common pollutant in coking wastewaters, on anammox processes and microbial communities in anammox reactors for over two years of continuous exposure. The addition of SCN − (from 50 to 200 mg L −1 ) showed negative effects on the denitrification performance of the anammox reactors. In SCN − -dosed reactors, increased effluent ammonium concentrations indicated the occurrence of SCN − -based biodegradation processes. Microbial analysis revealed that the anammox species almost disappeared in the reactor dosed with SCN − at over 100 mg L −1 . Instead, an abundance of chemolithoautotrophic bacteria belonging to the Thiobacillus genus demonstrated a linear increase with SCN − addition. The competition between anammox species and SCN − -degrading microorganisms was expected to dominate the inhibition effects of SCN − addition on the performance of anammox reactors.